An Investigation of Grade 12 Students’ Fundamental Understanding of Sequences through Problem Solving Activities at a Lao Demonstration Secondary School - Shingphachanh, Sommay (International Journal on Emerging Mathematics Education, 2025)
This study examined how grade 12 students solve problems involving the fundamental concept of sequences, identifying their conceptual understanding and the nature of their reasoning processes. This qualitative study collected the data from 21 students through mathematics problem activities on triangular, square, and cube number sequences. Findings revealed that students often determined the fourth term by summing the first three terms and struggled to generalize patterns. Most relied on visual counting and extended linear or square patterns to cubic contexts without grasping the exponential nature of cube numbers. Overall, students showed limited ability to identify and generalize numerical patterns. The study recommends instructional strategies that integrate visual, numerical, and conceptual representations to deepen understanding of numerical patterns, linking visual representations with symbolic expressions to address misunderstandings. This study suggested further research on enhancing conceptual understanding through multiple representations and digital learning tools in secondary mathematics.